Application of green tea waste with fibrolytic enzyme and phytase on layer performance and egg quality - Chumkam, S.; Jintasataporn, O.; Triwutanon, S. (Journal of the Indonesian Tropical Animal Agriculture, 2021)
This study aimed to  investigate the effect of green tea waste, fibrolytic enzymes (xylanase and cellulase) and phytase  supplementation in layer  diets on   performance and egg quality. The experiment was assigned in a 2×3 factorial arrangement by completely randomized design.  Factor A consisted of two types  of diets: a) a basal diet without any green tea waste   and b) a basal diet with 1% of green tea waste.  Factor B consisted of three  levels of enzymes: a) level 0X, no enzyme supplementation; b) level 1X, a combination of fibrolytic enzymes,  24,000 FAXU xylanase and 100 ECU cellulase, and 1,000 FTU phytase; and c) level 2X, combination of fibrolytic enzymes,  48,000 FAXU xylanase and 200 ECU cellulase, and 2,000  FTU phytase.  One hundred  and ninety- two   Roman  Brown hens, aged 52 weeks, were randomly distributed to  six   groups and four replications. Layer hens were fed commercial diets with green tea waste and fibrolytic enzymes added on top as assigned in the treatment. The results showed that  green tea waste   significantly  increased (p<0.05) egg production, egg mass, feed conversion,  and Haugh unit.   In addition, green tea waste  tended  to affect (p=0.07) TBAs value.  Furthermore, the enzyme level significantly decreased  (p<0.05) feed intake and TBAs value.  In conclusion, the supplementation of 1% of green tea waste and 2X enzymes can  improve feed  conversion   and  the antioxidative  property of  eggs.